The Cultural Brand Strategy of Xinyang, China, from the Perspective of an International Garden City: Opportunities and Challenges - Wei, Zhang; Mastika, Lamat (Architectural Image Studies, 2025)
This paper takes Xinyang City, China, which was awarded the title of International Garden City, as the entry point to explore Xinyang's opportunities and challenges regarding cultural brand strategy in depth. By analyzing the advantages of Xinyang in terms of natural resources, historical culture, ecological construction, etc., this paper expounds on its favorable conditions for shaping cultural brands. Meanwhile, considering the current actual situations, such as market competition and cultural dissemination, analyze the challenges it faces. In response to these opportunities and challenges, strategic suggestions are put forward for cultural brands, aiming to provide references for Xinyang to enhance the city's cultural soft power and international competitiveness. This study, through various research methods such as field investigation, literature collection, data collection from government official websites, and questionnaire surveys, found that Xinyang City's ability to win the honorary title of International Garden City proves that Xinyang has relatively favorable conditions in terms of natural conditions, humanistic history, and urban construction. However, it also provides opportunities and challenges for the construction of its urban cultural brand. Through in-depth research, it is found that the popularity of Xinyang's urban cultural brand is not high, the competitive pressure is large, the exploration of the characteristics of cultural brands is not in-depth enough, the development of the cultural industry lags, and the dissemination of cultural brands is insufficient. Therefore, it is concluded that Xinyang needs to strengthen the dissemination of urban cultural brands, deeply explore the characteristics of cultural brands, promote the development of the cultural industry, and implement a differentiated competition strategy. This research is conducive to enhancing the cultural brand of Xinyang City and has certain reference significance for the construction of cultural brands in other cities.